Electrodeposition of CuNiS as battery type electrode for supercapacitor applications - Davut Uzun; Ahsen Albaş; Seyfullah Madakbaş; Ece Kök Yetimoğlu (Electrochemistry Communications)
This study focuses on the high-performance, binder-free electrodes on nickel foam by simple cathodic electrodeposition using nickel chloride, copper sulfate, and thiourea solution as aqueous electrolytes. The CuS, NiS, and NiCuS electrodes synthesized by cathodic electrodeposition were characterized by X-ray diffraction, energy dispersive spectra, and scanning electron microscopy. The electrochemical performance of the synthesized positive electrodes was investigated in aqueous potassium hydroxide electrolyte by widespread electroanalytical techniques such as cyclic voltammetry, electrochemical impedance spectroscopy, and galvanostatic charge-discharge. The electrochemical tests revealed that the synthesized electrode materials exhibited significant reversible redox reactions. Among the produced electrodes, CuNiS exhibited high specific capacitance (1026.9 F g−1 at 5 mV s−1; 1338.5 F g−1 at 1 A g−1 current density). The produced NiCuS//activated carbon supercapacitor achieved 890 W kg−1 power and 14.9 Wh kg−1 energy density in the potential range from 0 to 1.40 V. The asymmetric supercapacitor reached 157.8 % of the initial discharge capacity at the end of 5000 charge-discharge cycles. The results of this study indicate that the electrodes produced by the cathodic electrochemical deposition method have excellent potential for use as positive electrodes in supercapacitor applications.